IDDF2020-ABS-0016 Clinicopathologic characteristics and treatment outcomes of rectal gastrointestinal stromal tumors: experience from a tertiary center. (18th November 2020) - Lu, Yi; Sun, Jiachen; Chen, Honglei; Chen, Junrong; Kong, Xianhe; Zhong, Weijie
Abstract : Background: To investigate the clinicopathologic characteristics, surgical and imatinib management and long-term follow-up outcomes of the rectal gastrointestinal stromal tumors (GISTs). Methods: C onsecutive patients with rectal GISTs admitted in our center (from January 2013 to June 2018) were chosen. Their history information was viewed, and the follow-up results were obtained by phone or medical records. Results: Forty-nine patients (32males and 17 females) were identified, with a median age of 59 years, and 36 patients received surgery. Most (46 patients, 93.9%) of the tumor were located within 6 cm from the anal verge, 18 patients (36.7%) had very low or low risk, and 31patients (63.3%) had intermediate or high risk. Four kinds of surgery approach were applied in our center: trans-abdominal (8 patients, 22.2%), trans-anal/trans-perineal (15 patients, 41.7%), trans-sacral (12 patients, 33.3%) and abdominal perineal (1 patient, 2.8%). The complication is low, and the mortality related to surgery is 0%. After a median follow-up of 705 days (ranged from 48 days to 1677 days), 3 patients (8.33%) were found to have a recurrence. Conclusions: T rans-anal/trans-perineal and trans-sacral surgery were more commonly used in our study, and for now, the recurrence rate had no difference, but longer time for follow-up time is needed.